On the idea of potency : juridical and theological roots of the Western cultural tradition / Emanuele Castrucci. - Castrucci, Emanuele (Encounters in law and philosophy., 2016)
Emanuele Castrucci bridges the two seemingly unrelated worlds of classical Greek philosophy and Jewish biblical exegesis. He connects them through the historical nexus of Christianity, which has marked the destiny of Western philosophy across the political, philosophical and jurisprudential horizons.